Academic research as an optional final assignment: Legal analysis and educational consequences - Amrullah, Muhammad Karim; Triyana, Heribertus Jaka (LPMPP Universitas Negeri Yogyakarta, 2025)
This article aims to evaluate the concept and implementation of government policy, making academic writing a mandatory final assignment option for students. The evaluation focuses on related laws and regulations, especially the Ministerial Regulation issued by the government since 2023. Therefore, this study is relevant by describing the policy, which has been in effect for almost a year. The policy is within the authority of the central government and relevant ministers. Apart from that, the policy is in line with one of the principles of higher education in an effort to keep up with changes and developments over time. However, some provisions are not in sync with the Ministerial Regulation, which forms the legal basis for implementing the policy. Apart from that, the policy deviates from the concept of education and higher education and existing laws and regulations which regulate education and higher education. This research is normative research from a legal perspective and covers the field of education. This research technique was carried out by means of a literature review, which analysed regulations, theories, and expert opinions from a legal and educational perspective.